2017
DOI: 10.1007/s12029-017-9983-0
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis: Use of Statins Is Associated with a Reduced Incidence of Oesophageal Adenocarcinoma

Abstract: PurposeLaboratory studies have suggested that statins may have useful anti-cancer effects against Barrett’s epithelial cancer lines. A variety of effects have been reported in clinical studies.MethodsWe performed a systematic review and meta-analysis of the association between statin use and the development of oesophageal cancer. Multiple databases were searched for studies reporting the association of statin use and oesophageal cancer. Meta-analysis on the relationship between statin use and cancer incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…However, no evidence regarding this association is available. In addition, in recent years, several publications have hypothesized that statin use reduces esophageal and gastric cancer risk [39][40][41]. We recommend future studies to take these factors into account as well.…”
Section: Discussionmentioning
confidence: 93%
“…However, no evidence regarding this association is available. In addition, in recent years, several publications have hypothesized that statin use reduces esophageal and gastric cancer risk [39][40][41]. We recommend future studies to take these factors into account as well.…”
Section: Discussionmentioning
confidence: 93%
“…However, a recent study by Thrift et al showed that regular (at least once weekly) use of any NSAIDs was not associated with the risk of BO [86]. Studies have shown that regular statin use was inversely associated with the development of OAC and BO [87][88][89][90]. Studies have also shown that use of lower oesophageal sphincter relaxing drugs like nitroglycerin, anticholinergics, and b-adrenergic agonists was positively associated with risk for OAC [91,92].…”
Section: Medicationsmentioning
confidence: 99%
“…A 2017 meta-analysis of 11 studies, comprising almost 19,000 patients with BE, showed an OR of 0.59 of EAC among statin users, with consistent effects seen across all included studies (95% CI 0.50–0.68) [ 56 ]. This benefit might be dose-related, as Beales et al [ 57 ] demonstrated a reduced OR of EAC in patients taking high-dose statin therapy (equivalent to simvastatin 40 mg daily or higher) compared with that in those taking low-dose therapy (OR 0.31, 95% CI 0.05–0.97 vs OR 0.54, 95% CI 0.27–0.98).…”
Section: Candidate Chemoprevention Therapies For Esophageal Adenocarcmentioning
confidence: 99%